GENETIC CONTROL OF FERTILITY RESTORATION IN CMS LINES OF FLAX (LINUM USITATISSIMUM) - E. A. Porokhovinova (Труды по прикладной ботанике, генетике и селекции)
Three flax lines: gc-204 (with opened flowers, curved stamen filaments, sterile anthers, forming few seeds by selfpollination), gc-208 and gc-188 (fertile ones, sterility occurs only when hybridized with other lines) were used as CMS sources. These lines can be involved in heterosis breeding. Genes controlling male fertility restoration RFO8, RFO9 were identified. Recessive alleles of the genes restoring fertility rft3-2, rft3-3, rft3-6, rft3-7, rft5-2, rft6, rft7 and dominant RFT4-3 determine tubular shape of sterile flowers, and are undesirable for breeding because the probability of cross pollination decreases. Other recessive (alternative) alleles of pollen fertility restoration genes rfo6, rfo6-2, rfo6-3, rfo7 do not affect the corolla’s shape.